UPAYA PENINGKATAN RASA NASIONALISME DENGAN PENDIDIKAN KEWARGANEGARAAN KEPADA GENERASI MUDA DI ERA PERKEMBANGAN TEKNOLOGI - Andika Kavin Septiano; Fatma Ulfatun Najicha (Jurnal Global Citizen : Jurnal Ilmiah Kajian Pendidikan Kewarganegaraan, 2022)
The development of technology is something that cannot be avoided. Technological developments have more or less affected our daily lives. With the development of technology, our lives have been made easier. One of the conveniences offered is the ease of finding information and finding it easy. With the existing facilities, we can access various information and culture very easily. With very easy access to culture and information, we must be able to sort out which ones are in accordance with the culture and norms that exist in Indonesia. We must have love to love our homeland so that we are not easily influenced by cultures that are not in accordance with the norms and culture that exist in Indonesia. Civic education here plays an important role in instilling the spirit of nationalism and love for the homeland as early as possible to the younger generation.